Cordycepin induces M1/M2 macrophage polarization to attenuate the liver and lung damage and immunodeficiency in immature mice with sepsis via NF-κB/p65 inhibition. (27th November 2021) - Zhang, Yudan; Cheng, Jing; Su, Yufei; Li, Mingyue; Wen, Jun; Li, Sixiu
Abstract: Objectives: To explore the impacts of cordycepin and underlying mechanism on the sepsis. Methods: The sepsis mice model was built and treated with different concentrations of cordycepin. Then the liver and lung injury caused by cecal ligation and puncture (CLP) was assessed using H&E staining and TUNEL assay. The expression of relevant genes was detected using qRT-PCR analysis and ELISA assays. Besides, the macrophage polarization was checked by flow cytometry. Key findings: Cordycepin could significantly improve the liver and lung injury. Moreover, cordycepin increased the distribution of F4/80 + CD206 + M2-like macrophages and F4/80 + iNOS + M1-like macrophages through down-regulating the expression of relevant genes. More importantly, cordycepin could monitor the protein expression of iNOS, Arg-1, TNF-α, MCP-1, IL-4 and IL-10 in CLP mice. Meanwhile, the elevated level of p65 induced by CLP was also repressed by the increase of the cordycepin. Moreover, cordycepin played a crucial part in CLP mice through modulating the NF-κB/p65 signalling pathway. Conclusions: Cordycepin played an important role in mice with sepsis via reducing the M1/M2 macrophage polarization and modulating the NF-κB/p65 signalling pathway.